Nelda Graciela Arzú Ramírez (1964…) A garifuna teacher identified with her people and her culture - López Rivas, Oscar Hugo; Rodríguez, Humberto (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper presents the fruitful professional life of a teacher identified with the history and culture of her people, she constantly makes efforts for their promotion and development by overcoming difficulties and establishing bonds between her teaching performance and the comunity. Nelda’s efforts to get a degree, led her to choose the teaching career among the few options existing in her municipality. She decided to become a teacher by vocation, to serve her culture, which gave her the concepts and frames of reference for the interpretation of her world: the Garifuna culture. The work emerged in the frame of the research project entitled African and African Descendant Teachers in Colombia, Brazil, Guatemala, Venezuela, Equatorial Guinea in the century XX-XXI, within a research line on Latin American Educators. Life history method and qualitative approach were applied. Several interviews were conducted with Nelda, with people who know her and some relatives. Field visits were carried out, and impressions on her performance were released by people who have known her. As a member of the Garifuna people, the teacher Nelda has had an outstanding projection. She influences from her teacher position and her worldview, on the cultural, political and social life of the community by promoting a more accurate education regarding the linguistic and cultural reality of her people. Her teaching practices include curriculum construction, production of texts in Spanish and Garifuna language, she also boosts teachers training in bilingualism and multiculturalism for their professional practice.